Role of Strategic Management Accounting In Decent Work And Economic Growth In The Context Of Sustainable Development Goals (SDGs) - Delima Ramdani; Ricky Agustian; Yanuar Ramadhan (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This investigation aims to examine the function of strategic management accounting in supporting the achievement of Sustainable Development Goal (SDG) number 8, which emphasizes economic progress and good jobs. Methodology: This study employs a literature review methodology from various national and international journals to analyze the connection between sustainable development objectives and strategic management accounting procedures. Results: The results of the analysis show that strategic management accounting has an important contribution in creating an economic system that is transparent, accountable, and free from corruption. The strategic function of accounting is not only limited to financial reporting, but contributes to planning, controlling, and evaluating policies that encourage increased labor productivity and community welfare. Findings: Through the integration of financial, social, and environmental information, strategic management accounting can be a tool for policy formulation and decision-making that is in line with the principles of sustainability. Novelty & Originality: The novelty of this study lies in its systematic synthesis of strategic management accounting practices within the framework of SDG 8, an integration that has received limited attention in prior literature. Its originality emerges from the comprehensive examination of how accounting mechanisms can serve as drivers for decent work, competitiveness, and sustainable economic expansion in the Indonesian context. Conclusions: Thus, strategic management accounting serves as a major driver for achieving decent work, increased competitiveness, and sustainable, equitable economic expansi